Korean Model for Post-acute Comprehensive rehabilitation (KOMPACT): The Study Protocol for a Pragmatic Multicenter Randomized Controlled Study on Early Supported Discharge - Chang, Won Kee; Kim, Won-Seok; Sohn, Min Kyun; Jee, Sungju; Shin, Yong-Il; Ko, Sung-Hwa; Ock, Minsu; Kim, Hyun Joo; Paik, Nam-Jong (Frontiers in Neurology, 2021)
Introduction: Early supported discharge (ESD) is a transitional care model aimed at facilitating post-acute stroke patients' discharge to home. Previous studies have demonstrated that ESD provides equivalent patient and caregiver outcomes with superior cost-effectiveness compared to conventional rehabilitation (CR). This study intends to examine the feasibility of ESD in Korea. Methods and Analysis: This study is designed as a multicenter assessor-blinded, randomized controlled trial. Ninety post-acute stroke patients with mild to moderate disability (modified Rankin Scale 1–3) will be recruited from three university hospitals (30 patients per hospital) in Korea and allocated to either the ESD group or the CR group in a 1:1 ratio. Patients in the ESD group will receive individualized discharge planning and goal setting, a 4-week home-based rehabilitation program, and liaison service to community-based resources by a multidisciplinary team. Patients in the CR group will receive rehabilitation practices according to their current hospital policy. Outcomes: The primary outcome is the Korean version of the modified Barthel Index, and the primary endpoint was post-onset 3 months. Clinical outcomes, patient/caregiver reported outcomes, and socioeconomic outcomes will be measured at baseline, 1 month after discharge, 2 months after discharge, and 3 months after onset. Discussion: The efficacy and cost-effectiveness of ESD can vary according to the healthcare system and sociocultural aspects. To establish ESD as an alternative transitional care model for post-acute stroke patients in Korea, its feasibility needs to be examined in prior. This study will add evidence on the applicability of ESD in Korea. Ethical Considerations: The study protocol was reviewed and approved by the Institutional Review Board of Seoul National University Bundang Hospital (IRB number B-2012/654-308). The study protocol was registered at ClinicalTrials.gov (Identifier NCT04720820). Disseminations will include submission to peer-reviewed journals and presentations at conferences.